2020
DOI: 10.18510/hssr.2020.8516
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Covid-19 on Project Delivery: A Perspective From the Construction Sector in the United Arab Emirates

Abstract: Purpose of study: The study aimed at establishing the implications of the COVID-19 pandemic on project delivery in the UAE with a significant focus on the construction industry. The study also sought to determine some of the negative implications of COVID-19 for the construction industry. Methodology: The within-subjects research design was employed in the study. Purposive and simple random sampling was used in the selection of the respondents. A total of 116 project managers in the construction industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Because the construction industry is the backbone of the UAE's economy, measuring the effects of this pandemic on the overall performance of construction projects is of utmost importance (Mashreq, 2020). Ghandour (2020) aimed at establishing the implications of COVID-19 on project delivery from the perspective of the construction industry of the UAE. Results suggested that there is a significant increase in the required days to complete the project owing to the inaccessibility to raw material and labor.…”
Section: Covid-19 and Its Implications On Construction Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Because the construction industry is the backbone of the UAE's economy, measuring the effects of this pandemic on the overall performance of construction projects is of utmost importance (Mashreq, 2020). Ghandour (2020) aimed at establishing the implications of COVID-19 on project delivery from the perspective of the construction industry of the UAE. Results suggested that there is a significant increase in the required days to complete the project owing to the inaccessibility to raw material and labor.…”
Section: Covid-19 and Its Implications On Construction Industrymentioning
confidence: 99%
“…World leaders are collaborating to introduce and implement measures that garner positive results and ensure a safe environment and the well-being of their citizens to enable economies to gradually revive (Yam et al, 2020). Similarly, the United Arab Emirates (UAE) has taken precautionary measures to reinforce the safety of its residents and measures that directly affect the performance of ongoing construction projects (Ghandour, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Nicola et al (2020) emphasised that the impact of COVID-19 on global healthcare systems has a cascading effect on every area of human existence. In order to halt the spread of COVID-19, governments around the world have implemented a series of preventive steps (Ghandour, 2020), including avoiding unnecessary travel, social distancing, and prohibiting congregations (Nicola et al, 2020). Accordingly, as people, communities, governments, academic institutions, and industrial enterprises grapple with the problems of reducing human life loss in the face of an unseen pandemic, and the practice of social distance has pervaded daily life (Sarkis et al, 2020).…”
Section: Impact On Construction Industrymentioning
confidence: 99%
“…The COVID-19 pandemic has had an impact on the construction sector, as it has on many other industries, in many different ways (Raoufi and Fayek, 2021). Similarly, Ghandour (2020), andZamani, Rahman, Fauzi, andYusof (2021) agreed that the construction industry has been impacted by COVID-19. 1, there are many challenges for the construction industry as a result of the COVID-19 pandemic.…”
Section: Impact On Construction Industrymentioning
confidence: 99%
See 1 more Smart Citation